A TRIZ-based approach to manage innovation and intellectual property. (1st January 2011) - Regazzoni, D.; Rizzi, C.; Nani, R.
In this paper, we present a methodology and a working paradigm, based on TRIZ theory, specifically conceived for SMEs that are not able to face the problem of intellectual property management (IPM) in an autonomous way. As a first step, we introduce the competences and possible company structure to manage and protect intellectual property (IP) by means of patents and trademarks; then we describe the methodologies and the tools, which can be used for IPM, such as those derived from TRIZ. Finally, we describe a case study which refers to a typical example of know-how transfer from a technological leading sector to the large production of consumable products showing the use of considered TRIZ tools.